2021
DOI: 10.1021/jacs.1c07095
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Enhancement of a Natural 14–3–3 Protein Ligand

Abstract: Rational design of protein–protein interaction (PPI) inhibitors is challenging. Connecting a general supramolecular protein binder with a specific peptidic ligand provides a novel conceptual approach. Thus, lysine-specific molecular tweezers were conjugated to a peptide-based 14–3–3 ligand and produced a strong PPI inhibitor with 100-fold elevated protein affinity. X-ray crystal structure elucidation of this supramolecular directed assembly provides unique molecular insight into the binding mode and fully alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Supramolecular systems can provide orthogonal molecular elements for enhancing affinity and selectivity in protein recognition and modulation by targeting protein elements such as side chains and peptide motifs [108]. Combining synthetic supramolecular elements with peptide recognition motifs would therefore provide an elegant and unique entry for the development of such improved tool compounds, and we report here a first successful proof of concept (Figure 25) [109]. Selective recognition of proteins and modulation of their interactions represents an unprecedented opportunity for pharmacological innovation, but the rational design of protein-protein interaction (PPI) modulators remains challenging, mostly due to the different structural characteristics of protein interfaces compared to traditional drug targets [107].…”
Section: Modification Of Carbon Surface To Enhance Removal Of Cadmium From Aqueous Solution (P15)mentioning
confidence: 84%
See 1 more Smart Citation
“…Supramolecular systems can provide orthogonal molecular elements for enhancing affinity and selectivity in protein recognition and modulation by targeting protein elements such as side chains and peptide motifs [108]. Combining synthetic supramolecular elements with peptide recognition motifs would therefore provide an elegant and unique entry for the development of such improved tool compounds, and we report here a first successful proof of concept (Figure 25) [109]. Selective recognition of proteins and modulation of their interactions represents an unprecedented opportunity for pharmacological innovation, but the rational design of protein-protein interaction (PPI) modulators remains challenging, mostly due to the different structural characteristics of protein interfaces compared to traditional drug targets [107].…”
Section: Modification Of Carbon Surface To Enhance Removal Of Cadmium From Aqueous Solution (P15)mentioning
confidence: 84%
“…Supramolecular systems can provide orthogonal molecular elements for enhancing affinity and selectivity in protein recognition and modulation by targeting protein elements such as side chains and peptide motifs [108]. Combining synthetic supramolecular elements with peptide recognition motifs would therefore provide an elegant and unique entry for the development of such improved tool compounds, and we report here a first successful proof of concept (Figure 25) [109]. Here, we show for the first time the interfacing of a synthetic supramolecular element (lysine-specific molecular tweezers) with an ExoS peptide recognition motif to furnish a powerful ditopic 14-3-3 ligand exhibiting up to a 100-fold improved affinity.…”
Section: Modification Of Carbon Surface To Enhance Removal Of Cadmium From Aqueous Solution (P15)mentioning
confidence: 84%
“…It has been widely applied to modulate protein functions ( Bier et al, 2013 ; Schrader et al, 2016 ; Trusch et al, 2016 ; Vopel et al, 2017 ; Wilch et al, 2017 ; Mittal et al, 2018 ; Li et al, 2019 ; Bengoa-Vergniory et al, 2020 ; Weil et al, 2020 ; Brenner et al, 2021 ). Additionally, the optimization of CLR01 has gained considerable attention ( Dutt et al, 2013a ; Dutt et al, 2013b ; Klarner and Schrader, 2013 ; Heid et al, 2018 ; Herrera-Vaquero et al, 2019 ; Guillory et al, 2021 ; Li et al, 2021 ; Meiners et al, 2021 ). The 14-3-3 proteins are composed of nine antiparallel α-helices ( Yang et al, 2006 ) and are target proteins for the tweezer ( Figure 1B ).…”
Section: Introductionmentioning
confidence: 99%
“…The binding of tweezers to 14-3-3 proteins is a representative example of supramolecules regulating protein functions. Several experimental and theoretical studies have investigated the binding events between tweezers and 14-3-3 proteins ( Bier et al, 2013 ; Bier et al, 2017 ; Shi and Xu, 2019 ; Guillory et al, 2021 ). Via isothermal titration calorimetry (ITC), Bier et al found that tweezers exhibited at least two binding events with different affinities to 14-3-3σ ( Bier et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation